Optimizing Eri Silkworm Productivity: Evaluating the Performance of Ecoraces of Samia ricini (Donovan) in the East Coastal Condition of Tamil Nadu, India - Anujaa.B; Arivudainambi.S (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigated raising Eri silkworms, Samia ricini (Donovan) a multi-voltine, domestic moth, traditionally bred indoors and known for its spun silk, in the eastern coast of Tamil Nadu, India. Eri silkworms typically thrive in the northeast regions, but the growing demand for Eri silk has led to exploring new locations for their production. The eight ecoraces of Eri silkworm i.e. C2, Borduar, Khanapara, Mendipathar, Dhanubanga, Nongpoh, Borduar and Titabar were selected for this study reared on castor plants under varied climatic conditions in Tamil Nadu. The economic and grainage characters such as larval duration, matured larval weight, survival rate, cocoon weight, shell weight, shell ratio, effective rearing rate, rate of pupation, rate of moth emergence, fecundity and hatchability were analyzed. This study revals that C2 ecorace consistently outperformed the other ecoraces, exhibiting superior growth parametrics, cocoon quality, and silk production potential.Findings indicate that optimal temperature and humidity conditions are crucial for enchancing performace, particularly for sensitive ecoraces like Barpathar and Nongpoh, highlighting the importance of ecorace selection and environmental management for sustainable eri silk production.